Impact of minimal residual disease status in patients with relapsed/refractory acute lymphoblastic leukemia treated with inotuzumab ozogamicin in the phase III INO-VATE trial. (January 2020) - Jabbour, Elias; Gökbuget, Nicola; Advani, Anjali; Stelljes, Matthias; Stock, Wendy; Liedtke, Michaela; Martinelli, Giovanni; O'Brien, Susan; Wang, Tao; Laird, A. Douglas; Vandendries, Erik; Neuhof, Alexander; et al.
Highlights: Subgroup data were analyzed in patients with ALL enrolled in INO-VATE (NCT01564784). The analysis was based on MRD status at end of treatment with inotuzumab ozogamicin. MRD-negative patients with complete remission had improved survival vs MRD-positive. MRD-negative patients treated in 1st salvage experienced the most survival benefit. The best outcomes were seen in these patients who proceeded to stem cell transplant. Abstract: Minimal residual disease (MRD) negativity is a key prognostic indicator of outcome in acute lymphocytic leukemia. In the INO-VATE trial (clinicaltrials.gov identifier: NCT01564784), patients with relapsed/refractory acute lymphocytic leukemia who received inotuzumab versus standard chemotherapy achieved greater remission and MRD-negativity rates as well as improved overall survival: hazard ratio 0.75, one-sided P = 0.0105. The current analysis assessed the prognostic value of MRD negativity at the end of inotuzumab treatment. All patients who received inotuzumab ( n = 164) were included. Among patients with complete remission/complete remission with incomplete hematologic response (CR/CRi; n = 121), MRD-negative status (by multiparametric flow cytometry) was defined as <1 × 10 –4 blasts/nucleated cells. MRD negativity was achieved in 76 patients at the end of treatment. Compared with MRD-positive, MRD-negative status with CR/CRi was associated with significantly improved overall survival and progression-free survival, respectively: hazard ratio (97.5% confidence interval; one-sided P- value) 0.512 (97.5% CI [0.313–0.835]; P = 0.0009) and 0.423 (97.5% CI [0.256–0.699]; P < 0.0001). Median overall survival was 14.1 versus 7.2 months, in the MRD-negative versus MRD-positive groups. Patients in first salvage who achieved MRD negativity at the end of treatment experienced significantly improved survival versus that seen in MRD-positive patients, particularly for those patients who proceeded to stem cell transplant. Among patients with relapsed/refractory acute lymphocytic leukemia who received inotuzumab, those with MRD-negative CR/CRi had the best survival outcomes.